2016
DOI: 10.1039/c6ra08551b
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-controlled synthesis of WO2.72 nanostructures and their photocatalytic properties

Abstract: WO2.72 nanowires and urchin-like WO2.72 nanostructures exhibited enhanced photocatalytic activities for organic pollutants degradation compared to commercial nanostructured tungsten oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Guo et al (2011b) reported WO 2.72 nanorods synthesized hydrothermally by reducing the as-obtained (NH 4 ) x WO 3+x/2 and using sulfate as a capping agent in an atmosphere of H 2 (5 vol%)/N 2 at 500 • C for 1 h. The solvothermal method was extensively studied for WO 2.72 for different nanostructures. WO 2.72 nanowires were synthesized by a simple solvothermal method using WCl 6 and ethanol solution under 180 • C for 10-24 h (Qin et al, 2011b;Xi et al, 2012;Guo et al, 2016). Cetyltrimethylammonium bromide has also been used as a growth-directing agent to fabricate WO 2.72 nanowires (Li et al, 2016a).…”
Section: Solvothermal Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al (2011b) reported WO 2.72 nanorods synthesized hydrothermally by reducing the as-obtained (NH 4 ) x WO 3+x/2 and using sulfate as a capping agent in an atmosphere of H 2 (5 vol%)/N 2 at 500 • C for 1 h. The solvothermal method was extensively studied for WO 2.72 for different nanostructures. WO 2.72 nanowires were synthesized by a simple solvothermal method using WCl 6 and ethanol solution under 180 • C for 10-24 h (Qin et al, 2011b;Xi et al, 2012;Guo et al, 2016). Cetyltrimethylammonium bromide has also been used as a growth-directing agent to fabricate WO 2.72 nanowires (Li et al, 2016a).…”
Section: Solvothermal Methodsmentioning
confidence: 99%
“…Only disordered nanoparticles were formed at a low temperature (120 • C) even when sufficient WCl 6 was provided. This demonstrated that the morphology can be fine-tuned by controlling variables such as time, precursor concentration, and temperature (Guo et al, 2016). synthesized WO 2.72 urchin-like nanostructures and nanowires by treating WCl 6 with ethanol under 180 • C for 10 h. WO 2.72 nanowires were obtained when the precursor concentration was 0.5 g L −1 and the reaction time was 10 h. Control of different morphologies by adjusting the concentration of precursor was discussed in this study.…”
Section: Solvothermal Methodsmentioning
confidence: 99%
“…Tungsten oxide, which shares perovskite units, has attracted much attention for thermocatalysis, photocatalysis, and photoelectrocatalysis [1,2]. Tungsten oxide is well known for its oxophilic nature, which renders the lattice capable of withstanding numerous oxygen deficiencies in the bulk without compromising the crystal phase stability and allows the formation of a series of tungsten sub oxides (WOx such as WO2.92, WO2.84, and WO2.72) [3][4][5]. Intriguingly, WOx is favored for a variety of applications, as oxygen vacancies can serve as shallow donors and modify the electronic structure of tungsten oxide, thus enhancing the dispersion of supported active metal sites [6] and adsorption of surface species (H2, CO2, alcohols etc.)…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Tungsten oxide has been widely investigated as a new functional material, due to its crucial applications in chromic devices, gas sensors, photo-catalysts, super-capacitors and eld emission devices. [13][14][15][16][17][18][19] WO 3 nanostructure lms, coated by noble metals such as Pt or Pd as catalysts, have shown high sensitivity to H 2 in air at room temperature, and good repeatability. [20][21][22][23] Particularly, the Pt, Pd or their oxide particle-coated WO 3 lms composed of one-dimensional nanostructures (such as nanowires, nanorods, nanoneedles, nanobers and nanotubes) have been proved to have a more outstanding performance in hydrogen detection in previous reports by our group 24,25 and other groups.…”
Section: Introductionmentioning
confidence: 99%